Influence of harvesting season and post harvest storage time on carotenoid biosynthesis in Malaysian orange sweet potato (ipomoea batatas) tuber flesh - Othman, Rashidi; Kammona, Suhair; Jaswir, Irwandi; Jamal, Parveen (2015)
Carotenoid content in plants differs due to several factors such as cultivar, maturity, climatic, geographic effects, and storage. Improving the nutritional values of sweet potato is an important breeding goal and understanding the regulation, genetics and inheritance of carotenoid biosynthesis is vital to achieve this. Environmental conditions can have a marked influence on the accumulation of carotenoids in sweet potato tubers. Little is known about the effects of post harvest storage time and harvesting season particularly on carotenoid biosynthesis. Therefore this study aimed to investigate the effects of year of harvest and storage time on carotenoid biosynthesis in Malaysian orange sweet potato tuber flesh. The results showed that orange sweet potato tubers contained α-carotene and β-carotene in the first harvesting season, whereas lutein and zeaxanthin were the most common carotenoids detected in second harvesting season. Analysis of carotenoid profiles of the orange sweet potato tubers grown in two different seasons confirmed that the harvesting season had a major effect on the total carotenoid content and the individual carotenoid compounds. The post harvest storage of sweet potato tubers over 3 period of time appears to have distinct effects on carotenoid biosynthesis, the magnitude of the effects being dependent on the time of storage. Results show that storage for 1 and 6 months resulted in the accumulation of α-carotene, β-carotene, lutein and zeaxanthin with a concomitant decreased of lutein, β-carotene and total carotenoid content. Results of this study will help to understand the effects of year of harvest and storage time on carotenoid biosynthesis in orange sweet potato tubers.